Strategi Pengembangan Ekonomi Syariah UMKM untuk Perekonomian Lokal Bekasi (Jurnal Ekonomi Bisnis dan Akuntansi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) represent a fundamental pillar and the backbone of Indonesia’s economy, contributing significantly by accounting for approximately 61% of the Gross Domestic Product (GDP) and absorbing up to 97% of the total national workforce. Despite their strategic role, MSMEs consistently face systemic challenges that hinder their growth, particularly related to limited access to capital, technology, and broader markets. This study posits that the Islamic economic framework, with its fundamental principles such as justice (‘Adl), partnership, and risk-sharing, offers a structurally more compatible paradigm for addressing these challenges. Using Bekasi Regency as a case study—an area with strong macro-industrial dominance but paradoxically high unemployment rates—this research analyzes the disconnection between economic growth at the upper level and entrepreneurial development at the grassroots level. The study proposes an integrated ecosystem model that involves synergy among local governments, Islamic financial institutions, and MSME communities. Key findings indicate that a shift from debt-based financing to partnership and profit-sharing models aligned with Sharia, such as Mudharabah and Musharakah, can unlock significant and more inclusive growth potential. The journal concludes with specific and actionable policy recommendations to foster a resilient and just local economy through Sharia-based MSME development strategies